Evolutionary Analysis of the LAFL Genes Involved in the Land Plant Seed Maturation Program - Han, Jing-Dan; Li, Xia; Jiang, Chen-Kun; Wong, Gane K.-S.; Rothfels, Carl J.; Rao, Guang-Yuan (Frontiers in Plant Science, 2017)
Seeds are one of the most significant innovations in the land plant lineage, critical to the diversification and adaptation of plants to terrestrial environments. From perspective of seed evo-devo, the most crucial developmental stage in this innovation is seed maturation, which includes accumulation of storage reserves, acquisition of desiccation tolerance, and induction of dormancy. Based on previous studies of seed development in the model plant Arabidopsis thaliana, seed maturation is mainly controlled by the LAFL regulatory network, which includes LEAFY COTYLEDON1 (LEC1) and LEC1-LIKE (L1L) of the NF-YB gene family, and ABSCISIC ACID INSENSITIVE3 (ABI3), FUSCA3 (FUS3), and LEC2 (LEAFY COTYLEDON2) of the B3-AFL gene family. In the present study, molecular evolution of these LAFL genes was analyzed, using representative species from across the major plant lineages. Additionally, to elucidate the molecular mechanisms of the seed maturation program, co-expression pattern analyses of LAFL genes were conducted across vascular plants. The results show that the origin of AFL gene family dates back to a common ancestor of bryophytes and vascular plants, while LEC1-type genes are only found in vascular plants. LAFL genes of vascular plants likely specify their co-expression in two different developmental phrases, spore and seed maturation, respectively, and expression patterns vary slightly across the major vascular plants lineages. All the information presented in this study will provide insights into the origin and diversification of seed plants.